Dividends and Expropriation in Hong Kong - Janice C. Y. How; Peter Verhoeven; Cici L. Wu (Asian Academy of Management Journal of Accounting and Finance, 2008)
This study seeks to understand how dividend policy is related to ownership and control structure in Hong Kong, where family-controlled firms are widespread. Using data from a sample of 324 listed Hong Kong firms in 2005, our results show that a firm's propensity to pay dividends and the amount of payout decrease with divergence of the controlling shareholder's cash flow rights from control rights. Small to medium size family-controlled firms are significantly more likely to pay dividends and have higher dividend payouts than large family-controlled firms; however, this is moderated by the discrepancy between the controlling shareholder's cash flow rights and voting rights. This study provides empirical support for the expropriation hypothesis. Important academic implications include the need for a more accurate measure of potential expropriation and the need to control for firm size in tests of the relationship between payout policy and ownership structure and control. This study offers insights to policy makers interested in enhancing the legitimacy of corporate governance within their nation. In particular, it highlights that improvements in corporate governance will be most beneficial in smaller firms, where potential expropriation is greatest.